A Framework for Constructing Equity-Risk-Mitigation Portfolios. Issue 3 (23rd July 2020) - Baz, Jamil; Davis, Josh; Sapra, Steve; Gillmann, Normane; Tsai, Jerry
Abstract : The key trade-off among equity-risk-mitigation strategies is their expected return versus their ability to diversify equity risk. In particular, the more reliable a strategy's equity-hedging properties, the lower its expected return, and vice versa. This article proposes a framework for optimal equity-risk-mitigation portfolio construction. In our model, the investor maximizes the portfolio's unconditional expected return, subject to a constraint on its conditional equity beta. We show that the return to a risk-mitigation portfolio can be decomposed into hedging and return- generating components. We then demonstrate that optimal risk-mitigation portfolios exhibit better return-defensiveness properties relative to the underlying strategies. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 17 June 2019 Accepted 14 April 2020 by Stephen J. Brown